Mortalities of right whales and related anthropogenic factors in South African waters, 1963-1998 - Best, Peter B.; Peddemors, Victor M.; Cockcroft, Victor G.; Rice, Nan (J. Cetacean Res. Manage., 2020)
Between 1963 and 1998, 55 mortalities of southern right whales and a further three ‘possible right whale’ mortalities were recorded on the South African coastline. Of the known right whale mortalities, 31 could be classified as ‘calves of the year’, 8 as juveniles and 14 as adults. Relatively few (6.5-16.1%) of the calf mortalities could be attributed to anthropogenic factors, compared to juveniles (25-50%) and adults (35.7-57.1%). Apparent causes of death included ship strikes (4 definite, 7 possible) and entanglement (4 definite, 1 possible), with one harpooning incident. Five non-fatal ship strikes and 16 instances of non-fatal entanglement were also recorded. Whilst the gear most commonly involved in non-fatal entanglement was crayfish trap lines, three of the four entanglement fatalities involved longline gear. The incidence of scars attributable to previous entanglement remained constant amongst mature females from 1979-1997, at 3-4%. Recorded mortalities increased over the period 1963-1997 at a rate no different from that of population growth over the same period. The current level of anthropogenic mortality does not seem to be affecting population recovery.